Legal Certainty of Expired Customary Land Ownership Rights in the Indonesian Agrarian Law System - Ridwan Jaelani; Waway Warsiman; Kahfi Purwana Graha (JURNAL PEMULIAAN HUKUM, 2023)
Disputes or conflicts cannot be avoided in a developing society, conflicts will inevitably occur which will eventually turn into disputes. Disputes regarding the ownership of land rights are certainly not a problem that has just emerged, it has been several decades that have adorned agrarian conflicts in Indonesia since the Basic Agrarian Law was promulgated. Problems then arise in terms of a dispute that creates legal uncertainty against owners of customary land rights which are said to be expired or past time in the agrarian law system in Indonesia. The term expiration of customary land rights is not known in the national agrarian law for acquiring or relinquishing customary land rights. In other words, a principle has arisen that contradicts the provisions of the national agrarian law regulations applied in society. This is what causes legal uncertainty in society which can become a bad precedent in the future regarding the same problem and harm the purpose of the law itself.Sengketa atau konflik tidak dapat dihindari dalam suatu masyarakat yang sedang berkembang, konflik pasti akan terjadi yang pada akhirnya akan berubah menjadi sengketa. Sengketa mengenai kepemilikan hak atas tanah tentu bukan masalah yang baru saja muncul, sudah beberapa dekade konflik agraria menghiasi konflik agraria di Indonesia sejak Undang-Undang Pokok Agraria diundangkan. Permasalahan kemudian muncul dalam hal sengketa yang menimbulkan ketidakpastian hukum terhadap pemilik hak atas tanah adat yang dikatakan daluarsa atau lewat waktu dalam sistem hukum agraria di Indonesia. Istilah hapusnya hak atas tanah adat tidak dikenal dalam hukum agraria nasional untuk memperoleh atau melepaskan hak atas tanah adat. Dengan kata lain, timbul suatu asas yang bertentangan dengan ketentuan peraturan hukum agraria nasional yang berlaku di masyarakat. Hal inilah yang menimbulkan ketidakpastian hukum dalam masyarakat yang dapat menjadi preseden buruk di kemudian hari terkait masalah yang sama dan merugikan tujuan hukum itu sendiri.